Acquired right ventricular outflow tract aneurysm in pulmonary atresia and intact ventricular septum: a nidus for thromboembolism. (31st July 2018) - Boutsikou, Maria; Fraisse, Alain; Shore, Darryl; Voges, Inga
Abstract: Pulmonary atresia with intact ventricular septum may be complicated by coronary aneurysms and myocardial ischaemia. We report a case of an acquired postoperative right ventricular outflow tract aneurysm with communication to the left ventricular outflow tract. Multimodality imaging helped in the characterisation of this structural abnormality, which led to treatment modification of the patient.